Budaya Literasi Melalui Gesigeli (Gerakan Siswa Gemar Literasi) - Susi Handayani (Universitas Sebelas Maret, 2020)
Reading an interest in the student must be done in a manner continuing when not done on a regular basic and discliplined it would not have formed a good literary culture. When reading culture is assimilated into students, it builds up an optimal literative character. Developing attitudes and characteristics often require the support of all parties of government, school, teachers, parents, and environment and yourself. If all parties can collaborate and assist in establishing an orderly attitude and custom, then is a virtue.